Characteristics of intra-annual distribution of precipitation and incoming water and the synchronization analysis of their changes in the lower reaches of the Yangtze river basin - Kaidong, Lu; Tingting, Cui; Yintang, Wang; Yong, Liu (Frontiers in Earth Science, 2024)
Precipitation and incoming water are the key contributing factors to local flooding events, and analyzing the intra-annual distribution and change characteristics of precipitation and incoming water will be beneficial to the understanding of flooding contributing factors in this region. In this paper, the characteristics of intra-annual distribution of precipitation and incoming water and the synchronization of their changes in the lower reaches of the Yangtze River Basin (LYRB) from 1980 to 2020 are studied using the concentration degree and concentration period as quantitative indicators. The results are as follows: (1) the maximum precipitation occurs earlier in the year, while maximum incoming water occurs with little variation in timing but significant variation in total volume; (2) the concentration degree of both precipitation and incoming water show a slowly decreasing trend. The concentration period of precipitation is slightly advanced, and that of incoming water is significantly delayed;(3) the occurrence time and concentration period of the incoming water peak during 2010-2020 lagged behind that of precipitation, which played a role in suppressing the occurrence of floods in the LYRB. This study can provide a scientific basis for the future supply and demand of water resources in the LYRB for safe use.